Pendeteksian Gerak Menggunakan Sensor Kinect for Windows - Hartono Hartono; Liliana Liliana; Rolly Intan (Jurnal Infra, 2015)
Along with the rapid technology development, the usage of computer input tools is also on the rise. Starting from a keyboard which had specific message for each button, developed into touch screen technology which enables human to interact directly with the screen; now technology in which a mere gesture is enough to input a command to the computer is being developed. Gesture detection can be done by the utilization of several tools. For instance, Kinect is one of the tools which are equipped with depth sensor that is capable to recognize and tracking human joints.The system being made is consisted of skeletal tracking process toward user and motion detection. Skeletal tracking process had been provided by kinect sdk. That skeletal tracking is utilized to detect user's hand position. User's hand detection is used to detect the gesture that is done by the user. The making of this application is done by Microsoft Visual Studio C# WPF 2010 and Kinect Software Development Kit.Therefore, this thesis is aimed to make an application which is capable in gesture and hand position detection on certain areas. This application utilized Kinect as the media for command input. The process starts from the checking of position movement, which will be identified as swipe gesture later on. In addition, hand position detection in specific areas is also being utilized, in order to determine how wide those areas is able to be touched by hand, when the user's position is exactly in the centre of Kinect's sensor